Lymphocyte Polarization During Immune Synapse Assembly: Centrosomal Actin Joins the Game - Cassioli, Chiara; Baldari, Cosima T. (Frontiers in Immunology, 2022)
Interactions among immune cells are essential for the development of adaptive immune responses. The immunological synapse (IS) provides a specialized platform for integration of signals and intercellular communication between T lymphocytes and antigen presenting cells (APCs). In the T cell the reorganization of surface molecules at the synaptic interface is initiated by T cell receptor binding to a cognate peptide-major histocompatibility complex on the APC surface and is accompanied by a polarized remodelling of the cytoskeleton and centrosome reorientation to a subsynaptic position. Although there is a general agreement on polarizing signals and mechanisms driving centrosome reorientation during IS assembly, the primary events that prepare for centrosome repositioning remain largely unexplored. It has been recently shown that in resting lymphocytes a local polymerization of filamentous actin (F-actin) at the centrosome contributes to anchoring this organelle to the nucleus. During early stages of IS formation centrosomal F-actin undergoes depletion, allowing for centrosome detachment from the nucleus and its polarization towards the synaptic membrane. We recently demonstrated that in CD4+ T cells the reduction in centrosomal F-actin relies on the activity of a centrosome-associated proteasome and implicated the ciliopathy-related Bardet-Biedl syndrome 1 protein in the dynein-dependent recruitment of the proteasome 19S regulatory subunit to the centrosome. In this short review we will feature our recent findings that collectively provide a new function for BBS proteins and the proteasome in actin dynamics, centrosome polarization and T cell activation.